2012
DOI: 10.1123/jpah.9.7.1036
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Rheumatoid Arthritis: A Systematic Review

Abstract: Background: Physical activity is associated with improved health outcomes in many populations. It is assumed that physical activity levels in the rheumatoid arthritis (RA) population may be reduced as a result of symptoms of the disease. The objective of this review is to establish the current evidence base for levels of physical activity in the RA population. Methods: A systematic review was performed of 7 databases (Emabase, MEDLINE, AMED, Biomedical Reference Collection Expanded, CINAHL, Nursing and Allied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
80
2
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 56 publications
7
80
2
5
Order By: Relevance
“…Other studies (2,3,8,15) have shown either comparable or lower PA levels in RA patients than the general population, but these vary widely in disease activity, disease duration, age, sex, measurement tools, and cutoff values of national PA guidelines. Furthermore, some differences might be partly explained by cultural influences.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (2,3,8,15) have shown either comparable or lower PA levels in RA patients than the general population, but these vary widely in disease activity, disease duration, age, sex, measurement tools, and cutoff values of national PA guidelines. Furthermore, some differences might be partly explained by cultural influences.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our sample may represent a population between 2 extremes and provide a base for clinical decision-making and recommendations about HEPA. Obviously, there are several other studies on physical activity levels in RA, but the use of different measurement tools impedes specific comparisons between the studies (10). Established HEPA at baseline predicted being in the stable high trajectory versus the 2 other groups, and self-efficacy for exercise predicted being in the stable high versus the stable low group.…”
Section: Discussionmentioning
confidence: 99%
“…Many people with RA do not reach or maintain the recommended HEPA levels (8,9) and are less physically active than the general population (10,11). To explain and possibly influence physical activity behavior, numerous correlates in different domains have been identified in the general population (12) and in RA (13).…”
Section: Introductionmentioning
confidence: 99%
“…A well-established example is in patients with chronic inflammatory disorders such as arthritis and multiple sclerosis; exercise improves their mobility, lessens their pain and improves their mood (Motl and Pilutti, 2012;Tierney et al, 2012). Data from studies of rats suggest that running wheel exercise can enhance innate immune function by modulating the expression of cytokines and chemokines in white adipose cells (Speaker et al, 2013).…”
Section: Challenge 2: Runningmentioning
confidence: 99%